Image Segmentation Using an Evolutionary Method Based on Allostatic Mechanisms; Studies in Computational Intelligence; Vol. 630: Image Feature Detectors and Descriptors. Foundations and Applications - Osuna-Enciso V. Valentin; Zuniga V. Virgilio; Oliva Navarro D. A. Diego Alberto; Cuevas E. Erik; Sossa H. Humberto (2016, 2016)
Title screen